Эффективность некоторых методов оптимизации упруго-демпферных подвесок агрегатов - Филипковский, С. В. (НТУ "ХПИ", 2007)
The research is dedicated to optimization of suspensions defending the equipment of flight vehicles from g-loads. The purpose of activity is to check the efficiency of different optimization methods. The oscillations of a system with a linearly-elastic spring and non-linear damping are considered. An objective function is the maximum acceleration of suspended unit determined during the integration of the motion equation. The problem differs by that the objective function is rough and ravine, and range of varied parameters is jagged. The hybrid adaptive method of optimization allows to solve a problem of optimal synthesizing and displays a high efficiency in comparing with methods proposed in known FEM complexes.
Keywords: летательные аппараты; вибрации; перегрузки; амортизаторы; амортизирующая подвеска; гибридный метод оптимизации